Systematics : a Course of Lectures. - Wheeler, Ward C.; Wiley eBooks (Hoboken : John Wiley & Sons, 2012)
Systematics: A Course of Lectures is designed for use in an advanced undergraduate or introductory graduate level course in systematics and is meant to present core systematic concepts and literature. The book covers topics such as the history of systematic thinking and fundamental concepts in the field including species concepts, homology, and hypothesis testing. Analytical methods are covered in detail with chapters devoted to sequence alignment, optimality criteria, and methods such as distance, parsimony, maximum likelihood and Bayesian approaches. Trees and tree searching, consensus and s.
John Wiley and Sons
Keywords: Biology -- Classification; Biology -- Textbooks; Biology; Electronic books